2017
DOI: 10.1073/pnas.1620744114
|View full text |Cite
|
Sign up to set email alerts
|

A social insect perspective on the evolution of social learning mechanisms

Abstract: The social world offers a wealth of opportunities to learn from others, and across the animal kingdom individuals capitalize on those opportunities. Here, we explore the role of natural selection in shaping the processes that underlie social information use, using a suite of experiments on social insects as case studies. We illustrate how an associative framework can encompass complex, contextspecific social learning in the insect world and beyond, and based on the hypothesis that evolution acts to modify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 88 publications
0
52
0
Order By: Relevance
“…But given the evolutionary argument above, the demonstration need not imply that these associative learning mechanisms did not evolve beyond their basic state (see also ref. 47). Indeed, the argument suggests that associative learning mechanisms are the building blocks of cognitive evolution, and are finely tuned to serve new social, cultural, and other advanced functions (48).…”
mentioning
confidence: 99%
“…But given the evolutionary argument above, the demonstration need not imply that these associative learning mechanisms did not evolve beyond their basic state (see also ref. 47). Indeed, the argument suggests that associative learning mechanisms are the building blocks of cognitive evolution, and are finely tuned to serve new social, cultural, and other advanced functions (48).…”
mentioning
confidence: 99%
“…Hundreds of laboratory experimental studies have demonstrated social learning and transmission in a wide variety of animals. Social learning is now extensively documented in mammals (29), with a particular intensity of research studies in primates (30)(31)(32)(33) and cetaceans (34)(35)(36)(37), in birds (38)(39)(40)(41), in fish (42), and in insects (43,44). The fact that social learning has been shown to play important roles spanning multiple functional contexts (25)(26)(27)(28) suggests that many animals are not simply acquiring one or a few behavioral patterns socially, but rather that social learning is central to their acquisition of adaptive behavior.…”
Section: The Discovery Of Widespread Animal Culturementioning
confidence: 99%
“…Strategic information use is critical to the success of many animals. Animals must, for example, decide whether to explore new options, exploit the knowledge they already have, or use information gleaned from or sent by other animals about potential options [13]. Two important classes of information for animals are private information and social information.…”
Section: Introductionmentioning
confidence: 99%
“…Social insects, such as ants and bees, offer an unique system in which to study information use strategies [1,3], as social information use is likely to be very well developed in this group. More fundamentally, however, in many aspects of information use by social insects no conflict is expected within a colony.…”
Section: Introductionmentioning
confidence: 99%